1997
DOI: 10.2307/1271154
|View full text |Cite
|
Sign up to set email alerts
|

Applied Linear Statistical Models

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
609
2
34

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(649 citation statements)
references
References 0 publications
4
609
2
34
Order By: Relevance
“…Limitations in the research on OSA and neurocognitive function include inconsistent findings, small sample sizes, noncomprehensive test batteries, inadequate control groups, and short treatment durations. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] APPLES was designed to address these limitations by assessing the sham-controlled, long-term efficacy of CPAP therapy on neurocognitive function in a study with comprehensive tests of major neurocognitive domains and adequate statistical power. Using these study design parameters, we showed a difference between active vs. sham CPAP for only the E/F variable at 2 months.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations in the research on OSA and neurocognitive function include inconsistent findings, small sample sizes, noncomprehensive test batteries, inadequate control groups, and short treatment durations. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] APPLES was designed to address these limitations by assessing the sham-controlled, long-term efficacy of CPAP therapy on neurocognitive function in a study with comprehensive tests of major neurocognitive domains and adequate statistical power. Using these study design parameters, we showed a difference between active vs. sham CPAP for only the E/F variable at 2 months.…”
Section: Discussionmentioning
confidence: 99%
“…It first performs the F test on each separate feature together with data labels. Then it selects features according to the percentile of the highest F scores (Neter et al, 1996). Similarly, RFE also excludes the features with low relevance to label prediction, but the criteria refer to the weights derived from a certain classifier such as SVM (Guyon et al, 2002).…”
Section: Classification Analysismentioning
confidence: 99%
“…Before performing multiple OLS regression analysis, we conducted a multicollinearity test among the variables by using variance inflation factors (VIFs). The largest VIF value in the full moderated regression models was 1.48, which was well below the cutoff of five points supported by the literature (Neter et al, 1996), indicating that multicollinearity among the variables was not a concern (Hair et al, 1998).…”
Section: Hypotheses Testingmentioning
confidence: 51%